Insights into Second-Sphere Effects on Redox Potentials, Spectroscopic Properties, and Superoxide Dismutase Activity of Manganese Complexes with Schiff-Base Ligands - Palopoli, Claudia Marcela (2019)
Six Mn-Schiff base complexes, [Mn(X-salpn)]0/+ (salpn = 1,3-bis(sal-ic-ylidenamino)propane, X = H [1], 5-Cl [2], 2,5-F2 [3], 3,5-Cl2 [4], 5-NO2 [5], 3,5-(NO2)2 [6]), were synthesized and characterized in solution, and second-sphere effects on their electrochemical and spectroscopic properties were analyzed. The six complexes catalyze the dismutation of superoxide with catalytic rate constants in the range 0.65 to 1.54 × 106 M–1 s–1 obtained through the nitro blue tetrazolium photoreduction inhibition superoxide dismutases assay, in aqueous medium of pH 7.8. In solution, these compounds possess two labile solvent molecules in the axial positions favoring coordination of the highly nucleophilic O2•– to the metal center. Even complex 5, [Mn(5-(NO2)salpn) (OAc) (H2O)], with an axial acetate in the solid state, behaves as a 1:1 electrolyte in methanolic solution. Electron paramagnetic resonance and UV–vis monitoring of the reaction of [Mn(X-salpn)]0/+ with KO2 demonstrates that in diluted solutions these complexes behave as catalysts supporting several additions of excess O2•–, but at high complex concentrations (≥0.75 mM) catalyst self-inhibition occurs by the formation of a catalytically inactive dimer. The correlation of spectroscopic, electrochemical, and kinetics data suggest that second-sphere effects control the oxidation states of Mn involved in the O2•– dismutation cycle catalyzed by complexes 1–6 and modulate the strength of the Mn-substrate adduct for electron-transfer through an inner-sphere mechanism.